2019
DOI: 10.1155/2019/1958747
|View full text |Cite
|
Sign up to set email alerts
|

High-Molecular-Weight Glutenin 1Bx17 and 1By18 Subunits Encoded byGlu-B1iEnhance Rheological Properties and Breadmaking Quality of Wheat Dough

Abstract: The elasticity of wheat dough is mainly determined by high-molecular-weight glutenin subunits (HMW-GSs) encoded by Glu-1 loci. In this study, we performed the first comprehensive study on the effects of Glu-B1i-encoded 1Bx17 and 1By18 subunits on dough rheological properties and breadmaking quality by using a pair of Glu-B1 near-isogenic lines (NILs) ZM-NIL1 and ZM-NIL2. Comparative analysis of basic quality parameters, rapid visco analyzer (RVA) and farinograph parameters, and C-cell and loaf parameters showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Although interchain disulfide bonds are critical for stabilizing HMW-GS polymers, nuclear magnetic resonance studies indicate that hydrogen bonds mediated by glutamine side chains may also play an important role in gluten structure stabilization (Belton, 1994;Belton et al, 1995). A high content of glutamine residues has a high ability to form both intra-and intermolecular hydrogen bonds and positively affect dough elasticity (Belton, 1999;Guo et al, 2019). In the genotypes studied, changes in the content of glutamine were found (see Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…Although interchain disulfide bonds are critical for stabilizing HMW-GS polymers, nuclear magnetic resonance studies indicate that hydrogen bonds mediated by glutamine side chains may also play an important role in gluten structure stabilization (Belton, 1994;Belton et al, 1995). A high content of glutamine residues has a high ability to form both intra-and intermolecular hydrogen bonds and positively affect dough elasticity (Belton, 1999;Guo et al, 2019). In the genotypes studied, changes in the content of glutamine were found (see Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…Several alleles at the Glu-B1 locus have been previously used. Among them, Glu-B1f (encoding the subunit pair 1Bx13 + 1By16) and Glu-B1i (encoding the subunit pair 1Bx17 + 1By18) had a positive effect on the dough rheological properties and bread-making quality, observed through an increase in the gluten content and loaf volume [18]. Previous reports indicated that the transcripts of 1Bx7 OE encoded by Glu-B1al were overexpressed by an insertion of 43 bp in the promoter region and/or gene duplication [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that different allelic variants of the HMW-GS gene in wheat were significantly associated with wheat quality [ 8 ]. The subunits 1Ax1 or 1Ax2* at the Glu-A1 locus, 1Bx13 + 1By16, 1Bx17 + 1By18, 1Bx7 + 1By8, and 1Bx7 + 1By9 at the Glu-B1 locus, and 1Dx5+1Dy10 at the Glu-D1 locus were significantly and positively correlated with gluten viscoelasticity and strong dough properties, facilitating the formation of stronger gluten to improve the bread processing quality [ 9 , 10 ], whereas, null at the Glu-A1 locus, 1Bx6 + 1By8 and 1Bx20 + 1By20 at the Glu-B1 locus, and 1Dx2 + 1Dy12 at the Glu-D1 locus were associated with poor quality [ 11 , 12 , 13 ]. As the number of HMW-GS alleles is limited in wheat, identifying novel glutenin genes from related species and incorporating them to wheat could provide more genetic resources for improving wheat quality.…”
Section: Introductionmentioning
confidence: 99%